PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA PERUSAHAAN (Studi pada Perusahaan Consumer Goods Industry yang Terdaftar di Bursa Efek Indonesia Periode 2018-2022) - Putri, Sahitania Krisbandono; Prasetiono, Prasetiono (Faculty of Economics and Business Diponegoro University, 2024)
ABSTRACT This study aimed to examine the effect of the Corporate Social Responsibility components, namely economic, environmental and social components on firm performance which is controlled by firm size and leverage in consumer goods industry companies listed on the Indonesia Stock Exchange. Firm performance is measured using Return on Assets (ROA). The independent variables used in this research are the economic component of CSR (CSRI ECO), the environmental component of CSR (CSRI ENV), and the social component of CSR (CSRI SOC). The sample used in this study is consumer goods industry companies listed on the Indonesia Stock Exchange during the 2018-2022 period. The total sample was 31 companies taken using the purposive sample method. The analytical method used is multiple regression analysis with the IBM SPSS Statistics 27 program, which previously passed the classical assumption test. The research results show that the economic component of CSR (CSRI ECO) and the environmental component of CSR (CSRI ENV) have a positive and significant effect on company performance. Meanwhile, the social component of CSR (CSR SOC) has a negative and significant effect on company performance. In addition, the control variable firm size (SIZE) has a positive and significant effect on company performance, while leverage (DAR) has a negative and significant effect on company performance.